Assessment of Anatomical and Functional Macular Changes with Optical Coherence Tomography Angiography After Macula-Off Rhegmatogenous Retinal Detachment Repair. (3rd April 2021) - Christou, Evita Evangelia; Kalogeropoulos, Christos; Georgalas, Ilias; Stavrakas, Panagiotis; Christodoulou, Eleni; Batsos, Georgios; Stefaniotou, Maria
ABSTRACT: Purpose: To evaluate macular capillary plexus changes with OCT-angiography with regard to macular detachment duration in macula-off rhegmatogenous retinal detachment (RRD). Methods : 23 eyes of 23 patients were included in this retrospective case–control study and were divided into 2 groups. Group-A had a macular detachment duration of 0 to 10 days and group-B of 11 to 30 days. All eyes underwent a single successful pars plana vitrectomy (PPV) and gas tamponade. We analysed the OCT-A characteristics and visual outcomes at 12 weeks postoperatively in the 2 groups. The fellow eye was used as control. Results: Vessel density (VD) and flow density (FD) in the superficial capillary plexus (SCP) were significantly lower in group-B ( p  < .01) than in group-A and control. FAZ SCP in both groups was significantly larger than the control ( p  < .01), although it did not differ significantly between the two groups ( p  = 1.000). BCVA was significantly lower in group-B compared to group-A ( p  < .01). BCVA was positively correlated with VD SCP in group B ( p  = .015), but not in group-A. Postoperative BCVA had no correlation with FAZ SCP in both groups. Conclusions: The macular detachment duration could be a predicting factor of flow density in macular capillary plexus which in turn might be an indicator of visual outcomes in chronic cases.